EXOGENOUS APPLICATION OF GROWTH REGULATORS IN SNAP BEAN UNDER WATER AND SALINITY STRESS - Jesús R. Torres-García; J. A. Escalante-Estrada; M. T. Rodríguez-González; C. Ramírez-Ayala; D. Martínez-Moreno (Journal of Stress Physiology & Biochemistry, 2009)
Salinity and moisture limiting crop productivity due an imbalance between concentrations of auxins, gibberellins, cytokinin, ABA and ethylene. applications of growth regulators to alleviate salinity stress can be an economic and safe alternative to environment. The objective of this study was to determine the effect of salinity (0, 1000 and 2000 ppm of NaCl), soil moisture (30 and 60%) and exogenous application of growth regulators (control, 5 mL L-1 at the Beginning of flowering and 5 mL L-1 in vegetative stage + Beginning of flowering) and the combinations of three factors in snap bean (Phaseolus vulgaris L.). Concentrations of 2000 ppm reduced biomass and pod production in 35.5 and 45%, respectively. The humidity had no effects in biomass production and pod number. With the application of growth regulators in the vegetative stage + beginning of flowering, the weight and number of pods were increased. The greater biomass and yield was observed with 0 ppm, 60% humidity and application of growth regulators in the beginning of flowering. However, with: 1000 ppm, 30% of humidity and application in B. flowering, the biomass production was statistically similar. Our conclusion suggests that the application of growth regulators can be economical and easily applicable for farmers.